The Firm and the State in the Globalization Process - Belo Moreira, Manuel (The International Journal of Sociology of Agriculture and Food, 2021)
Globalization is a process which results from dynamic economic, political, cultural or religious forces. These forces are simultaneously shaping and reshaping the international division of labor, favoring or opposing capital accumulation, and pushing toward an increasing homogeneity of human behavior and consumption or attempts to resist this movement. However, the author maintains that the driving force is economic. More specifically, the critical agent in globalization is shown to be Transnational Finance Capital (TFC) (involving both Transnational Corporations and Transnational Banks).First, the characteristics and increasing importance of TFC is examined, which is necessary in delineating a framework for analyzing the relationship between TFC and the State, particularly as it is manifesting in the agri-food sector. This framework highlights the fact that dialectical relationships between TFC and nation-States vary in different socio-economic contexts. A qualitative typology is proposed in an attempt to describe the nature of these relationships at any particular moment. The article ends with an application of this typology to different relationship patterns established between TFC and the Portuguese nation-State.